Otolaryngology cases the University of Cincinnati clinical portfolio - Pensak, Myles L.; Hart, Catherine K.; Patil, Yash J. (Thieme, 2018)
In the tradition of the acclaimed first edition, experts from the University of Cincinnati's Department of Otolaryngology-Head and Neck Surgery present new case reviews. Every chapter presents patient-based scenarios to prepare practitioners for ENT cases they will encounter during rounds, rotations, and patient exams. By establishing a uniform algorithm in obtaining and utilizing discreet points of data, the authors encourage a disciplined approach to patient assessment and management options. Sections organized by anatomy and subspecialty enhance the ability to learn and retain knowledge. Fo.